Pengaruh Beban Kerja terhadap Kinerja Karyawan melalui Insentif sebagai Variabel Intervening pada Bank BTN Kantor Cabang Jambi - Fiska Putri Zulfani; Sumarni Sumarni; Fitri Widiastuti (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to describe and analyze the effect of workload on employee performance with incentives as an intervening variable on employees of Bank BTN Jambi Branch Office. The method used is descriptive and quantitative analysis with a sample of 50 respondents. Data were collected using a Likert Scale-based questionnaire, and the analysis was carried out using the Smart Partial Least Square (PLS) technique with the help of SmartPLS 4.0 software. The results of the study indicate that workload has a positive and significant effect on employee performance, workload has a positive and significant effect on incentives, incentives have a positive and significant effect on employee performance, and incentives are able to mediate the effect of workload on employee performance.